A review on the strategies for reducing the non-linearity caused by scattering on spectrochemical quantitative analysis of complex solutions. Issue 5 (27th May 2020) - Wan, Xinghua; Li, Gang; Zhang, Mengqiu; Yan, Wenjuan; He, Guoquan; Awelisah, Yussif Moro; Lin, Ling
Abstract: Spectrochemical quantitative analysis of complex solutions is of great significance to all walks of life. However, scattering components are difficult to avoid in complex solutions. According to the M + N theory, as long as the scattering component is contained in the solution, it will inevitably cause non-linearity between the acquired absorption spectrum and the content of any component. This non-linear relationship causes the existing spectral measurement methods to fail in severe cases. In addition, quantitative analysis of absorption spectra under strong scattering conditions still does not have an explicit function expression to describe the multivariate non-linearity between the content of each component and the spectrum. Therefore, the various calibration strategies are developed to handle the non-linearity. In this review, the methods can be classified into three categories: that's the methods to suppress non-linearity during the acquisition of spectral information, removing the non-linearity in the spectral data by preprocessing algorithms during spectral information processing and non-linear calibration approaches to directly model the non-linearity during the spectral modeling. The above methods are summarized in this review and future research directions have been discussed.